Hubungan Antara Komunikasi Keluarga Dan Persepsi Terhadap Pola Asuh Demokratis Orangtua Dengan Kepercayaan Diri Pada Remaja - Wulandari, Sarah; , Siti Nurina Hakim, S.Psi, M.Si, Psi (2017)
The purpose of this study were to determine relationship the communication of family with the self confidence on olescent and relationship the perception of parents emocraticarenting with self confidence on adolescent. The hypothesis 1) are a positive relationship between communication of family with self confidence on adolescent, 2) are a positiverelationship between perception of parents democratic parenting with self confidence on adolescent, 3) are a positive relationship between communication of family and perception of parents democratic parenting with self confidence on adolescent. Subjects in this study were 120 subjects aged 12-14 years. The measuring instruments used in this study are: a) Scale Self Confidence, 2) Scale Communication of Family and b) Scale Perception of Parents Democratic Parenting. Linearity test showed that the technique of data analysis in this study statistical receipts Non-parametric Spearman's. The results of analysis values of rxy1= 0,171 sig (1-tailed)= 0,031: 2= 0.015 (p<0,05), its means positive significant relationship between communication of family with self confidence, better the communication of family, the higher self confidence of adolescence. Value of rxy2= 0,118 sig (1-tailed)= 0,099: 2= 0.049 (p<0,05), its means positive significant relationship between perception of parent democratic parenting with self confidence of adolescence, more democratic of parents parenting, the higher self confidence of adolescence. Communication of Family,erception of Parents Democratic Parenting, Self Confidence in subjects classified as moderate. This is demonstrated by REmunication of family=50,02 and RH=42,5, while RE Perception of Parents Democratic Parenting=67,63 and RH=52,5. And Confidence=61,53 and RH=50. SE Communication of Family to Self Confidence= 2,92%. It is still 97,08% are other variables that may affect the Self Confidence. SE Perception of Parents ocratic Parenting to Self Confidence= 1,39%. It is still 98,61% are other variables that may affect the Self Confidence. For example mindset of individual, social factors and economic factors.